2014
DOI: 10.1007/s13181-014-0381-8
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Considerations in the Clinical Laboratory Assessment of Metals

Abstract: The presence of metals in the environment is ubiquitous and humans are constantly being exposed to them. As such, a general concern exists about potential health consequences that result from the exposure to metals. The continued efforts of environmental scientists to measure metals in clinical specimens are important for defining the extent of human exposure to these chemicals. Laboratory methods to measure the concentration of metals in human blood or urine are available, and they can be used to assess the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Typically, metals are measured in blood, urine or hair because these samples are easily procured from otherwise healthy individuals; however, interpretations about the timing of exposure vary by specimen. While blood is generally thought to assess recent exposure and urine a subacute or chronic exposure, these assumptions can vary based on the properties of the metal and other confounding factors such as age and health of the individual(67). For example, studies have shown that the kidney cortex is a high-affinity storage site for Cd (halftime varies between 18 and 44 years(68)) and that kidney Cd is slowly released into the urine at a rate of approximately 1.7% of total kidney Cd approximately every eight hours.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, metals are measured in blood, urine or hair because these samples are easily procured from otherwise healthy individuals; however, interpretations about the timing of exposure vary by specimen. While blood is generally thought to assess recent exposure and urine a subacute or chronic exposure, these assumptions can vary based on the properties of the metal and other confounding factors such as age and health of the individual(67). For example, studies have shown that the kidney cortex is a high-affinity storage site for Cd (halftime varies between 18 and 44 years(68)) and that kidney Cd is slowly released into the urine at a rate of approximately 1.7% of total kidney Cd approximately every eight hours.…”
Section: Resultsmentioning
confidence: 99%
“…21 Elevated serum aluminum concentrations might be misinterpreted if caused by environmental contamination during specimen collection or processing, as well as other nonanalytic or analytic issues. [14][15][16][17] While there is limited information about the frequency of this problem, results from this study suggest it may be a relatively common cause for abnormal serum aluminum concentrations. Owing to the retrospective study design, methods used by various facilities could not be determined.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Erroneous elevated results may also be caused by other factors such as mislabeling, reporting, or analytic problems such as problems with solution preparation or instrument malfunctions. 16,17 However, the frequency with which any of these potential problems lead to inaccurate serum aluminum measurements is unknown. False elevation in serum aluminum concentrations may cause misinterpretation of results and lead to unnecessary measures to check for sources of exposure, to conduct more intensive environmental testing, or may result in unnecessary treatment.…”
mentioning
confidence: 99%
“…Por otra parte, desde el punto de vista analítico, el índice de individualidad para una prueba de laboratorio se puede aumentar estratificando la población en grupos, lo que optimizaría la utilidad de la prueba. Existen además alternativas para evaluar diferencias en el monitoreo de un analito de los individuos, tal es el caso del Valor de Referencia del Cambio de un analito o xenobiótico específico, un método utilizado para interpretar una diferencia en las mediciones en un paciente, donde el resultado de la prueba actual se compara con los resultados pasados del paciente y no con un valor de referencia basado en la población [68].…”
Section: Universidad De Manizales -Facultad De Ciencias De La Saludunclassified